Pengembangan Instrumen Tes Literasi Sains di Sekolah Dasar - Amri, Nurzil (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to produce valid and reliable scientific literacy test instruments on the topic of light. The test instrument development model uses the ADDIE (Analyze, Development, Design, Implementation and Evaluation) model. Scientific literacy test instruments were analyzed based on validity, reliability, level of difficulty and different power of questions using the help of Anaates V4 software. The results of this study indicate that out of a total of 30 multiple choice questions, there are 21 or 70% of the questions declared valid and 9 or 30% of the questions declared invalid and the reliability score was 0.87 with a very strong category. The index of difficulty level of scientific literacy questions is moderate 53.33%, easy 30% and difficult 16.66%. on the different power test, scientific literacy questions with very good categories 10%, good 43.33%, enough 30% and bad 16.66%. Thus the scientific literacy test instrument on the material properties of light is appropriate to be used as a tool for assessing student competence.